Health consequences of cocaine use in France: data from the French Addictovigilance Network. (2nd October 2020) - Eiden, Céline; Vincent, Marc; Serrand, Chris; Serre, Anais; Richard, Nathalie; Picot, Marie‐Christine; Frauger, Elisabeth; Fouilhé, Nathalie; Daveluy, Amélie; Peyrière, Hélène; ,
Abstract: As the number and severity of complications related to cocaine use reported to the French Addictovigilance Network have increased, the French health authorities requested a national epidemiologic study of the data collected by this network from 2010 to 2016. For this purpose, the spontaneous reports (SRs) linked to cocaine notified by health professionals were analyzed as well as the data from the pharmacoepidemiological surveys OPPIDUM (observation of illegal drugs and misuse of psychotropic medications) and DRAMES (deaths related to the abuse of licit and illicit psychoactive substances). In total, 1 265 SRs were analyzed (510% increase from 2010 to 2016). Users were mainly men (952/1 261; 75%), with a median age of 35.0 years [IQ25–75 : 28–42]. Cocaine was consumed through the intranasal route by 52% of users (416/797), followed by intravenous administration (32%, 253/797) and inhalation (24%, 190/797). The use of cocaine powder and crack cocaine was reported in 70% (475/674) and 23% (154/674) of SRs, respectively. Cocaine was consumed with other psychoactive substances and alcohol in 47% (603/1265) and 60% (387/649) of cases, respectively. The main cocaine‐related complications were psychiatric complications (29%), neurologic complications (24%) and cardiovascular complications (23%). Analysis of the OPPIDUM survey data showed that in 2016, 15.9 and 2.4% of the included subjects consumed cocaine or crack cocaine the week preceding the survey, the highest rate for the 2006–2016 period. The DRAMES survey indicated that cocaine‐related deaths increased by threefold from 2014 to 2016. These data confirm that cocaine use in France is worrying with an increase in the number of severe complications and deaths.